2012
DOI: 10.1111/j.1741-6612.2012.00632.x
|View full text |Cite
|
Sign up to set email alerts
|

Neuropsychiatric effects of Parkinson's disease treatment

Abstract: Advances in the treatment of Parkinson's disease have led to significant improvement in many of the disabling motor symptoms of the disease, but often at the cost of neuropsychiatric side-effects. These include psychosis, dopamine dysregulation syndrome, impulse control disorders, mood disorders and Parkinson's disease drug withdrawal syndromes. Such side-effects can be as disabling and have as much impact on activities of daily living, quality of life, relationships and caregiver burden as motor symptoms. Awa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
12
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 20 publications
2
12
0
Order By: Relevance
“…In addition, we also observed that higher percentage of treatment with dopamine agonist was associated with increasing severity of frontal behavioral changes in PD patients. This is consistent with previous evidences that dopamine agonist treatments in PD are associated with increased risk of behavioral changes and neuropsychiatric symptoms [25,26] , especially impulse control disorders [27] .…”
Section: Discussionsupporting
confidence: 81%
“…In addition, we also observed that higher percentage of treatment with dopamine agonist was associated with increasing severity of frontal behavioral changes in PD patients. This is consistent with previous evidences that dopamine agonist treatments in PD are associated with increased risk of behavioral changes and neuropsychiatric symptoms [25,26] , especially impulse control disorders [27] .…”
Section: Discussionsupporting
confidence: 81%
“…None of these therapies have, so far, shown to be getting any closer to preventing disease progression and are, therefore, essentially symptomatic or palliative. Despite the efficacy of dopaminergic therapies in improving motor function and overall quality of life, they fail to prevent disease progression, and are associated with important complications [8][9][10]. This is consistent with the notion that the upstream molecular processes responsible for the cascade of pathological events are not yet being targeted by therapies currently available or under clinical development.…”
supporting
confidence: 61%
“…Impulse control disorders as well as mere symptoms of ICBs may have a potentially negative impact on patients' quality of life, finances, and social functioning and induce an increased caregiver burden [10]. Thus it is of utmost clinical importance to quickly identify patients at risk for developing ICBs.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, it appears that despite the negative consequences of ICBs, patients seldom present symptoms to healthcare professionals, which may be related to patients underestimating or denying the presence and severity of ICBs [10,25,26] e.g. due to lack of insight [27] or unwillingness to reveal behavioral symptoms [28].…”
Section: Introductionmentioning
confidence: 99%